2006
DOI: 10.1016/j.jcis.2006.01.003
|View full text |Cite
|
Sign up to set email alerts
|

pH-dependent surface charging and points of zero charge

Marek Kosmulski

Abstract: The recently published points of zero charge (PZC) of various materials are compiled to update previous compilations [M. Kosmulski, Chemical Properties of Material Surfaces, Dekker, New York, 2001; M. Kosmulski, J. Colloid Interface Sci. 253 (2002) 77; M. Kosmulski, J. Colloid Interface Sci. 275 (2004) 214]. The recent results corroborate the previously found PZC with a few exceptions. The PZC of alumina obtained from the second-harmonic generation response is substantially lower than the PZC obtained by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
137
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(161 citation statements)
references
References 18 publications
21
137
1
2
Order By: Relevance
“…closer to the reported value of pH 8-10. 13,[24][25][26] In a recent study by Kershner et al, 16 it was shown that crystalline alumina powder with relatively uniform shapes (Sumitomo AA-2) has p.z.c. at pH 3.8, while random-shaped alumina powder They found that -Al 2 O 3 platelets with mainly (0001) surfaces had a p.z.c.…”
Section: Discussionmentioning
confidence: 99%
“…closer to the reported value of pH 8-10. 13,[24][25][26] In a recent study by Kershner et al, 16 it was shown that crystalline alumina powder with relatively uniform shapes (Sumitomo AA-2) has p.z.c. at pH 3.8, while random-shaped alumina powder They found that -Al 2 O 3 platelets with mainly (0001) surfaces had a p.z.c.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the IEP is less a parameter of the particle phase but rather a characteristic parameter of the suspension. In a couple of papers, Kosmulski reviewed experimentally determined PZC and IEP-values for numerous materials in varying environments (Kosmulski 2002(Kosmulski , 2004(Kosmulski , 2006(Kosmulski , 2009.…”
Section: Zeta-potentialmentioning
confidence: 99%
“…The nanoparticles of silica attained a negative charge by deprotonation at pH > 2 ( Fig. 1), and for alumina surfaces such deprotonation occurred at pH > 8 [31]. Thus, alumina surfaces and silica nanoparticles have surface charges with opposite sign between pH = 2 and 8 and thus experience an attraction by electric diffuse double layer interactions [32].…”
Section: Analysis Of the Deposition Kineticsmentioning
confidence: 99%